Iodine-Mediated Vicinal Difunctionalization of Alkenes: A Convenient Method for Building C–Se and C–S Bonds - Wang, Junxing; Sheng, Weijian; Yan, Jie (Synlett, 2018)
A novel I2-mediated procedure is developed for building C–Se and C–S bonds simultaneously from alkenes, diselenides and sodium dithiocarbamates. This difunctionalization of alkenes is carried out in the presence of I2 and air, and exhibits good characteristics such as being transition-metal-free, requiring mild reaction conditions and simple procedures. The approach provides the product β-selanylethyl dithiocarbamates with high regioselectivity and in good yields. A plausible electrophilic addition mechanism is hypothesized.
Keywords: difunctionalization of alkene; β-selanylethyl dithiocarbamate; alkene; diselenide; iodine-mediated